METODE PEMBELAJAAN DISKUSI DALAM PENINGKATAN KOMPETENSI PESERTA DIKLAT - Yosef P Koton (Universitas Muhammadiyah Gorontalo, 2015)
The Implementation of effective learning methods that expected to improve the effectiveness of teaching and learning can walk dynamically, so that the goals and objectives of any training material that given will be absorb as well as possible by the training participants. Thus the selection of appropriate learning methods is a necessity in learning process to improve the competence of training participants which is a blend of knowledge, skills, motivation, attitude and personal characteristics shown in behavior and the influence performance of the training participants. Use of discussion teaching method has many advantages, meanwhile, from the aspects that discussed by the participants can grow up even from the outside aspects which discussed by the lecturers. The increase of competence training participants in terms of knowledge is more focused on the understanding of science and to share experiences, while the competence of attitude measured with the change the behavior of training participants after join the training where they more be patient to face the society behavior, also the training of participant skills who have a skills in problem solving in his organization. Widyaiswara as a facilitator can determine the successful in improving the competence of training participants. Therefore the trainers should be able to do their duties in a professional manner with mastering the type of effective learning methods such as discussion teaching methods.